1996
DOI: 10.1021/ja9615738
|View full text |Cite
|
Sign up to set email alerts
|

Fluorophobic Effect Induces the Self-Assembly of Semifluorinated Tapered Monodendrons Containing Crown Ethers into Supramolecular Columnar Dendrimers Which Exhibit a Homeotropic Hexagonal Columnar Liquid Crystalline Phase

Abstract: The rational design, synthesis, and characterization of the building blocks obtained by the esterification of the first generation of tapered monodendrons 3,4,5-tris(p-dodecan-1-yloxy)benzoic acid (12-AG) and 3,4,5-tris[p-(n-dodecan-1-yloxy)benzyloxy]benzoic acid (12-ABG) containing semifluorinated dodecyl groups [i.e., 12Fn-AG-15C5 (n = 0, 4, 6, 8), 12Fn-AG-B15C5, 12Fn-ABG- 15C5, and 12Fn-ABG-B15C5 (n = 0 and 8) where n following the letter F represents the number of outer perfluorinated methylenic units of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
257
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 400 publications
(262 citation statements)
references
References 63 publications
4
257
1
Order By: Relevance
“…The close scaling of size (30,33), shape, and quasi-equivalency of surfaces (37)(38)(39) observed between nanoscale biostructures and various dendrimer families͞generational levels is both striking and provocative (30,40). These remarkable similarities suggest a broad strategy based on rational biomimicry as a means for creating a repertoire of structure-controlled, sizevariable, and shape-variable dendrimer assemblies.…”
mentioning
confidence: 94%
“…The close scaling of size (30,33), shape, and quasi-equivalency of surfaces (37)(38)(39) observed between nanoscale biostructures and various dendrimer families͞generational levels is both striking and provocative (30,40). These remarkable similarities suggest a broad strategy based on rational biomimicry as a means for creating a repertoire of structure-controlled, sizevariable, and shape-variable dendrimer assemblies.…”
mentioning
confidence: 94%
“…It has already been shown that cations can template the formation of ion-channel columnar architectures. Seminal work by Percec et al (15)(16)(17)(18)(19)(20) has demonstrated the self-assembly of dendronized crown ethers into ion channels via complexation of cations. The G-quartet, the hydrogen-bonded macrocycle formed by the self-assembly of four guanosines, is stabilized by cations.…”
mentioning
confidence: 99%
“…Each repeating units bears a branching point to which two or several new repeating units are attached. Owing to their unique properties such as solubility in water, well defined molecular architecture, and spherical shape, dendrimers and metallodendrimers have found numerous applications in chemical, physical and biological processes [16][17][18].…”
Section: A Brief Discussionmentioning
confidence: 99%